Adaptacja morfologiczna anglicyzmów w języku rosyjskim . - Rybczyńska, Magdalena (Przegląd Rusycystyczny, 2013)
Magdalena Rybczyńska Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Poland rybczynska.magda@gmail.com МОРФОЛОГИЧЕСКОЕ ОСВОЕНИЕ АНГЛИЦИЗМОВ В РУССКОМ ЯЗЫКЕ Резюме Освоение англицизмов в русском языке происходит на разных уровнях, начиная с фонологического, который позволяет определить грамматические категории заимствования. Следующий уровень это морфологическое освоение. В настоящей статьe доказывается, что слова усваиваются согласно правилам языка-реципиента. Анализ англицимов из „Комсомольской правды” подтверждает, что они принимают формы множественного числа и склоняются как русские слова. THE MORPHOLOGICAL ASSIMILATION OF ANGLICISMS IN RUSSIAN LANGUAGE Summary The adaptation of English loanwords into Russian takes place on different levels, starting with phonological one, which helps to decide on the category of anglicisms. The next step is morphological assimilation, which is proved here to follow the rules of the recipient lan-guage. The analysis of anglicisms used in the Russian newspaper shows that borrowings are adapted by native markers of declension, plurality and inflection. The paper also emphasises the influence of semantics and external factors on the assimilation process